2012
DOI: 10.1007/s12541-012-0011-9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of tool path planning in 5-axis flank milling of ruled surfaces with improved PSO

Abstract: Previous studies have shown that machining error in 5-axis flank milling can be systematically reduced by optimization of tool path planning. However, the solution quality of the optimization methods adopted by those studies was not satisfactory, due to the constraint that the cutter must contact the boundary curves of the ruled surface to be machined. This work proposes an improved tool path planning method based on Particle Swarm Optimization (PSO) algorithms without this constraint. The method enlarges the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…The number of interpolation between consecutive cutter locations also relates to the precision. The values of those parameters were chosen as recommended by the previous studies [3][4][5].…”
Section: Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of interpolation between consecutive cutter locations also relates to the precision. The values of those parameters were chosen as recommended by the previous studies [3][4][5].…”
Section: Test Resultsmentioning
confidence: 99%
“…Previous studies [2][3][4] have shown that meta-heuristic algorithms provide a systematic approach to controlling and reducing the geometrical deviations in 5-axis flank finishing cut of ruled surfaces through optimization of tool path planning. However, the optimization schemes based on ACS and various PSO algorithms failed to produce good search results due to high dimensionality of the solution space.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is expected that the proposed algorithm can effectively be applied to dynamic topology optimization to improve the convergence rate. 법으로부터 자연 모방 최적화 방법인 입자 군집 최적화 (particle swarm optimization: PSO) [3] , 개미 군집 최적화(ant colony optimization: ACO) [4] 그리고 인공벌 군집 알고리즘 (artificial bee colony algorithm: ABCA) [5] 등이 있다.…”
Section: Article Historyunclassified